O choro no Rio Grande do Sul : aspectos históricos, sonoros e socioculturais - Pompermaier, Alexandre (2022)
This thesis has as its theme the history of Choro in Rio Grande do Sul, considering the historical processes of arrival, settlement and expansion that began in the 19th century to consolidate from the first decades of the 20th century. In this perspective, an analysis is proposed that considers the historical, sociocultural and sound aspects that the genre presents in its different phases, considering both the spaces of practice of the genre and the performance of instrumentalists, composers, groups and their works. In addition, it seeks to reveal the approximations and distances that it presents with the sound manifestations of a regional character, considering the circularity of these artistic agents driven by the presence of cultural hybridism as an intrinsic phenomenon of this relationship. To carry out such analyzes, the concepts of cultural circularity, hybridism, border and notions such as musical "synthesis" and "historical cleavages" are used, believing that only through this methodology that relates History and Music as research fields will it be possible to understand this phenomenon. musical hybrid and plural sociocultural and sonically. In this sense, what is presented are the different moments and historical events that promote changes and transformations both in their formal and structural perspectives of gender in the regional and national spheres in the belief that in the scope of culture these exchanges are constant and dynamic. In the midst of this approach are the essentially sound elements that contemplate the relationships with regional sound manifestations essentially represented by nativist music in its various styles, genres and rhythms such as vaneira, chamaé, milonga among others that connect the spaces and artists who experience the cultural space of Rio Grande do Sul. It is believed in this way to reveal when, where and how Choro from the capital Rio de Janeiro arrives, settles and expands through the most varied regions of Rio Grande do Sul, marking a genre that in the first decades of the 21st century had dozens of groups and hundreds of instrumentalists and composers. Artists who, through their compositions and interpretations, pave the way for our analyzes about the presence or not of a stylistic aspect marked by sociocultural and sound traits from Rio Grande do Sul, sustained on the foundations of the cultural exchanges to which Brazilian music as a whole is constituted. In this sense, it is sought through all these perspectives and processes to contribute to the historiography of Choro in Rio Grande do Sul, having the knowledge that even contributing to reduce its historiographical gap, many doors remain open and many others have opened and, from this observation new research must emerge so that the genre can be even more discovered and presented to the general public.